EFEKTIFITAS PENGAWASAN HAKIM OLEH KOMISI YUDISIAL - Moch Ikhsan, Oddie; Syafingi, Habib Muhsin; Sintha Dewi, Dyah Adriantini (Varia Justicia, 2017)
Starting from the establishment of a suspect Candidate Former National Police Chief Pol Commissioner General Budi Gunawan then apply prapradilan to the South Jakarta District Court. Because the 77 Criminal Code stated determination of the suspect is not an object pretrial. In those articles which can be handled by pretrial regulated limitative, only for legitimate or not the arrest, detention, discontinuation or termination of the investigation and prosecution of compensation or rehabilitation for a criminal case was stopped at the level of investigation or prosecution. After a single judge South Jakarta District Court partially granted the petition Sarpin Rizaldi prapreadilan BG. In his judgment, Sarpin interprets the determination of the suspect as one of the pre-trial. Judge Sarpin Ats such action under the spotlight of the Judicial Commission for the above decision. The Judicial Commission then recommended to the Supreme Court Judge Sarpin to sanctions, but the Supreme Court rejected the recommendation because they have entered the realm of the judge's decision. The formulation of the problem in this study is How Model Judicial Oversight Committee, Oversight Problems To Know judge by the Judicial Commission, the Judicial Commission How the Implementation Monitoring and Oversight How effective implementation of the functions of the Judicial Commission in supervising judges and its influence on the judicial power. The method used in this research is using normative juridical approach, the specification of the research is descriptive analytical.Based on the findings of the Judicial Commission has the concept of preventive surveillance by the repressive, namely to prevent and then are giving emphasis and contain sanctions. The Judicial Commission has the authority to give the sanction of ethics recommendations to the Supreme Court but the repressive ie without the MA recommendations, the recommendations of the Judicial Commission to be worth sia. Cooperation and there is no obvious surgical realm between the Supreme Court and the Judicial Commission.